Rir para não chorar: análise e autocrítica no humor judaico - Feldman, Liana Ribemboim (2008)
This research has the purprose to characterize the Jewish mood based on the Freudian psychoanalysis. For that, the concept of chistes and mood developed by Freud were explained. Aiming a theoretical complementation for this study, the references of the comic mood found in the work of Henri Bergson were also used, in order to promote a wider understanding on the topic of the Jewish mood. This reserach points out the need of the Jewish mood in three great areas: as a form of ego defense in difficult situations, as release of aggressiveness in a licit way and, finally, as a verbal narrative passed on from generation to genereation, thus carrying through a group identification among the Jewish people